2006
DOI: 10.1007/s00432-006-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in functional status and survival in patients with acute myeloid leukaemia

Abstract: Acute myeloid leukaemia (AML) is mainly affecting elderly patients. Elderly patients are increasingly affected by impairment of functional status (FS). FS is of prognostic relevance for survival in different tumours. Data for patients with AML are rare. Within a prospective trial we recruited patients with newly diagnosed AML and measured FS by two different methods: Karnofsky performance status (KPS) and instrumental activities of daily living (IADL). Sixty-three patients aged 19-85 years (median 61.1) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 20 publications
0
57
1
2
Order By: Relevance
“…[13][14][15][16] Wedding et al found that impairment of instrumental activities of daily living was the single most predictive variable of survival in their sample of AML patients ages 19-85 years (median 61.1). 13 The ability to perform tasks necessary to live independently in the community, that is, shopping, food preparation, housekeeping, laundry, transportation, handling finances and medication bears most importantly on the survival of older adults. Muffly et al 15 found that the presence of slow walking speed and low mental health before transplant also have prognostic value for poorer survival.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…[13][14][15][16] Wedding et al found that impairment of instrumental activities of daily living was the single most predictive variable of survival in their sample of AML patients ages 19-85 years (median 61.1). 13 The ability to perform tasks necessary to live independently in the community, that is, shopping, food preparation, housekeeping, laundry, transportation, handling finances and medication bears most importantly on the survival of older adults. Muffly et al 15 found that the presence of slow walking speed and low mental health before transplant also have prognostic value for poorer survival.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Reported studies indicate that although age is important, performance status, associated comorbidities and impairment of functional status have a greater impact on survival. 12,13 Instrumental activities of daily living (IADL) was used for analyzing the functional status of 63 AML patients (median age 61.1, with a range of 19-85 years). 12 IADL was the single most predictive variable (hazard ratio (HR): 4.3, 95% confidence interval (CI) 1.7-10.5, P ¼ 0.001) on survival.…”
Section: Induction Therapymentioning
confidence: 99%
“…12,13 Instrumental activities of daily living (IADL) was used for analyzing the functional status of 63 AML patients (median age 61.1, with a range of 19-85 years). 12 IADL was the single most predictive variable (hazard ratio (HR): 4.3, 95% confidence interval (CI) 1.7-10.5, P ¼ 0.001) on survival. Although Karnofsky performance status (PS) (HR: 4.8, 95% CI 1.9-12.3, P ¼ 0.001) and an unfavorable cytogenetic risk group (HR:6.0, 95% CI 2.5-14.3, Po0.001) were significantly associated with survival, age did not independently affect survival.…”
Section: Induction Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…22 In another study, patients who reported needing assistance with instrumental activities of daily living at diagnosis had decreased survival, independent of age and KPS. 23 These data suggest that simple standardized measures to assess functional status can enhance the pretreatment evaluation for older adults. Further details on functional assessment will be described in the section on geriatric assessment (GA).…”
Section: Performance Status Strengths and Limitationsmentioning
confidence: 99%